Film - Schlozman, Steven (Arts for health, 2020)
Our world is inundated by film. Our best stories are told on movie screens, on televisions, on smartphones and laptops. Film argues that on-screen storytelling is the most ubiquitous format for art to intersect with health and well-being, offering a way for us to appreciate, understand and even celebrate the most nuanced and complex notions of what it means to be healthy through the stories that we watch unfolding. Clinicians use film to better understand their patients, and individuals use film to better understand themselves and each other. Using case histories and based on academic research from a range of disciplines, this book explores how film can be used by clinicians and healthcare practitioners to better understand patients; by individuals to better understand themselves and others; and - perhaps most important of all - by societies as a tool in the fight against the stigma of illness. This book not only makes the case that film keeps us healthy, but also tells us how. After all, nothing quite moves us like the movies.